Evaluasi User Experience Pada Aplikasi SIPATEN BPAFK Jakarta Menggunakan User Experience Questionnaire - Satrio Wibowo, Aryo; Basri, Hasan (Universitas Siber Indonesia, 2025)
The Medical Device Facility Security Information System (SIPATEN) application is a web-based application developed by BPAFK Jakarta to facilitate customers in submitting requests for proficiency testing services and testing and calibration of medical devices at BPAFK Jakarta. The observation shows that the SIPATEN application has never been evaluated thoroughly. The purpose of this study is to evaluate the user experience of the SIPATEN application using the User Experience Questionnaire (UEQ) method to determine aspects that need improvement and provide recommendations for improvement. The tools used for data analysis are UEQ Data Analysis Tool version 12 and SPSS 26 for instrument testing. The results showed that the perspicuity variable got the highest mean value (1.656), and the two variables that got low values were novelty (1.290) and stimulation (1.406). The recommendations given in this study relate to variables with low values, namely novelty and stimulation.